120k views
2 votes
What is the first step in solving the equation 3. 5 n + 6. 4 = 42. 5? add 6. 4 to each side of the equation. Subtract 6. 4 from each side of the equation. Multiply each side of the equation by 3. 5. Divide each side of the equation by 6. 4.

1 Answer

4 votes

Answer:

3.5n+6.4=42.5

-6.4=-6.4

3.5n=36.1

————— (divide)

3.5=3.5

n=36.1/3.5 or 10.314

Step-by-step explanation:

I'm confused by the question... is the question what is the first step of solving this equation?? and if it is, your answer is correct. which is subtract 6.4 for both sides.

User Radomeit
by
4.7k points